Modeling Business-friendly Policy in Lampung Province - Budi, Adi Asmariadi; Anggraini, Nova; Hasanudin, Sultan (Prosiding International conference on Information Technology and Business (ICITB), 2023)
Lampung Province Government has a target to build a business-friendly ecosystem in Lampung Province. Are the government development plans matched with the target which was stated in the government mission? This research has the aim to model the business-friendly policy in Lampung Province. An inductive qualitative method is used to model it. In-depth interview with purposive sampling used to gather primary data. Secondary data from legal/regulation related to research topics also gathered in this research. The model concludes that business-friendly policy has four corners/elements, among them are business initiation, business potency, business models/patterns, and business process. Each corner has branches that describe how to implement the model. The model can be used by the government to build a business-friendly ecosystem.Keywords—ease of doing business, business ecosystem, model, business-friendly policy